Pengaruh Corporate Social Responsibility (CSR) pada citra merek di PT. PLN(Persero) - Rosa Harimurti; Lindiawati Lindiawati (Journal of Business & Banking, 2017)
Corporate Social Responsibility (CSR) is one of strategicmarketing concept son social causes. The purpose of this study is to explain the influence of CSR’s dimension on di-mension of brand image in PLN Company in Indonesia. This study focuses on legal and ethical responsibilities that can enhance the positive functional and symbolic image. Sample of this study are 110 consumers that was chosen used on random sampling tech-niques in Mojokerto and data collected by questionnaires. The anlysis tool used is Partial Least Squares (PLS). The empirical results indicate that corporate legal responsibility has significantly effect on functionalimage but legal responsibility does not significantly effect on symbolicimage. Next, ethical responsibility has significant effect on both func-tionalimage and symbolicimage. Legal responsibility helps enhancing the functional image than symbolic image, meanwhile the ethical responsibility helps enhancing the symbolic image than functional image. The suggestion is that if firms should focus on one aspect of theCSR’s dimension to enhance the brand image.